2018
DOI: 10.1016/j.neuropsychologia.2018.03.027
|View full text |Cite
|
Sign up to set email alerts
|

The role of the right superior temporal gyrus in stimulus-centered spatial processing

Abstract: Although emerging neuropsychological evidence supports the involvement of temporal areas, and in particular the right superior temporal gyrus (STG), in allocentric neglect deficits, the role of STG in healthy spatial processing remains elusive. While several functional brain imaging studies have demonstrated involvement of the STG in tasks involving explicit stimulus-centered judgments, prior rTMS studies targeting the right STG did not find the expected neglect-like rightward bias in size judgments using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…In summary, although brainstem abnormality is found to be associated with the promotion of idiopathic RBD from experimental and clinical perspectives (Scherfler et al, 2011;Hanyu et al, 2012), there are no apparent volume changes of GM in the brainstem in PD patients with RBD compared with those without RBD. Previous studies have demonstrated the strong association of reduced GM volume changes in the right STG with weakened spatial processing (Ellison et al, 2004;Gharabaghi et al, 2006;Shah-Basak et al, 2018), narcolepsy (Joo et al, 2009;Weng et al, 2015), impaired emotion processing to support social interactions (Muller et al, 2008;Pan et al, 2015;Van de Vliet et al, 2018;Zhang et al, 2018), violent behaviors (Zhang et al, 2019), and some psychiatric disorders (Moreira et al, 2017;Zhao et al, 2017;Wang et al, 2018). Consistent with our result, sleep disorders and nocturnal violence in PD patients with RBD can be partially explained by GM volume reduction in the right STG.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In summary, although brainstem abnormality is found to be associated with the promotion of idiopathic RBD from experimental and clinical perspectives (Scherfler et al, 2011;Hanyu et al, 2012), there are no apparent volume changes of GM in the brainstem in PD patients with RBD compared with those without RBD. Previous studies have demonstrated the strong association of reduced GM volume changes in the right STG with weakened spatial processing (Ellison et al, 2004;Gharabaghi et al, 2006;Shah-Basak et al, 2018), narcolepsy (Joo et al, 2009;Weng et al, 2015), impaired emotion processing to support social interactions (Muller et al, 2008;Pan et al, 2015;Van de Vliet et al, 2018;Zhang et al, 2018), violent behaviors (Zhang et al, 2019), and some psychiatric disorders (Moreira et al, 2017;Zhao et al, 2017;Wang et al, 2018). Consistent with our result, sleep disorders and nocturnal violence in PD patients with RBD can be partially explained by GM volume reduction in the right STG.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have demonstrated the strong association of reduced GM volume changes in the right STG with weakened spatial processing (Ellison et al, 2004 ; Gharabaghi et al, 2006 ; Shah-Basak et al, 2018 ), narcolepsy (Joo et al, 2009 ; Weng et al, 2015 ), impaired emotion processing to support social interactions (Muller et al, 2008 ; Pan et al, 2015 ; Van de Vliet et al, 2018 ; Zhang et al, 2018 ), violent behaviors (Zhang et al, 2019 ), and some psychiatric disorders (Moreira et al, 2017 ; Zhao et al, 2017 ; Wang et al, 2018 ). Consistent with our result, sleep disorders and nocturnal violence in PD patients with RBD can be partially explained by GM volume reduction in the right STG.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, such decrease in activation is associated with more careful behavioral adjustment in response to the social stimulus, presumably to minimize error (i.e., executing the opposite action). Specifically, premotor areas (BA 6) and anterior cingulate cortex have been shown to activate parametrically to the neural computations of goal-directed actions (Fincham, Carter, Van Veen, Stenger, & Anderson, 2002;Gardini et al, 2016), while superior temporal regions have been robustly involved in visuo-spatial processing supporting motor planning (Hanakawa, Dimyan, & Hallett, 2008;Shah-Basak, Chen, Caulfield, Medina, & Hamilton, 2018). Overall, this is consistent with the down-regulation of a spatial processing and motor planning neural network likely to track the mental set of the prepotent stimulus-response behavior.…”
Section: Prestimulus Neural Impact Of Cuementioning
confidence: 53%
“…Support for STG involvement in spatial attention comes from neglect patients in whom impaired functional connectivity between STG and middle frontal gyrus (MFG) has been shown to correlate with the impaired interhemispheric parietal connectivity, which is in turn associated with the severity of the attentional deficit (He et al 2007). Consistent with lesion studies (Verdon et al, 2010) and both fMRI and TMS in healthy individuals (Galati et al, 2000;Neggers et al, 2006;Shah-Basak et al, 2018), STG inhibition by TMS affects allocentric, object-based, spatial processing (Ellison et al, 2004;Shah-Basak et al, 2018). It is noteworthy that the left STG cluster which increased RSFC with the right PPC seed is close to Heschl's gyrus, where early cortical auditory processing occurs (Tzourio et al, 1997).…”
Section: Discussionmentioning
confidence: 79%